Cochrane Database of Systematic Reviews 2009
DOI: 10.1002/14651858.cd006794.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Early amniotomy and early oxytocin for prevention of, or therapy for, delay in first stage spontaneous labour compared with routine care

Abstract: In prevention trials, early intervention with amniotomy and oxytocin appears to be associated with a modest reduction in the rate of caesarean section over standard care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
47
2
10

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(61 citation statements)
references
References 37 publications
2
47
2
10
Order By: Relevance
“…Yet no significant difference in duration of the second stage of labour was reported. A Cochrane systematic review showed that early augmentation of labour was associated with an increase in spontaneous vaginal births (Wei et al, 2009 Bugg et al, (2011) did not find any detectable adverse effects for mother or infant with oxytocin use. However several researchers have reported that women who were given synthetic oxytocin were less likely to achieve a spontaneous vaginal birth.…”
Section: Introductionmentioning
confidence: 99%
“…Yet no significant difference in duration of the second stage of labour was reported. A Cochrane systematic review showed that early augmentation of labour was associated with an increase in spontaneous vaginal births (Wei et al, 2009 Bugg et al, (2011) did not find any detectable adverse effects for mother or infant with oxytocin use. However several researchers have reported that women who were given synthetic oxytocin were less likely to achieve a spontaneous vaginal birth.…”
Section: Introductionmentioning
confidence: 99%
“…A c c e p t e d M a n u s c r i p t 6 6 We identified four meta-analyses grouping together randomized or quasi-randomized trials published between 1998 and 2013 on this topic [5][6][7][8]. The first meta-analysis focused on the combined effects of an early amniotomy and early prescription of oxytocin on the risk of cesareans in nulliparas.…”
Section: Page 6 Of 42mentioning
confidence: 99%
“…This first meta-analysis was updated in 2013 in the Cochrane Database [6], which excluded the studies with small sample sizes [9,10,11] and the two unpublished trials (Labrecque et al, Verkuyl et al). It also included 9 supplementary studies [8,[12][13][14][15][16][17][18][19][20][21][22][23].…”
Section: Page 6 Of 42mentioning
confidence: 99%
See 2 more Smart Citations